AN ANALYTICAL STUDY ON THE USER POWER OF INFLUENCER MARKETING, A NOVEL MARKETING APPROACH IN KERALA. - Karthika C. K., Prof. (Dr.) P. Ravindranath (Chelonian Research Foundation, 2023)
Today consumers place a greater emphasis on convergence, interaction, user control, and accessibility; these are the defining characteristics of new media. This causes the digital space to become more crowded. With the emergence of digital media, a new kind of transition has emerged in which brands provide an engaging and entertaining content to attract and retain customers’ attention. This is where the true brilliance of digital marketing is revealed, that is when consumers are willingly being involved and actively participate in the marketing activity. This has been a dilemma for marketers as their target customers continue to disperse across numerous social media platforms, making it increasingly difficult to reach them. Moreover, buyers today are well-informed and increasingly critical of brands’ marketing strategies; consequently, building trust is vital. Social media influencer marketing is the solution to the issue since it enables firms to discover and advertise directly to their target consumers. When talking about Kerala market, the most popular social media platform, Instagram plays a vital role in Influencer Marketing. Understanding the true potential of Instagram as one of the most influential social media platforms, and the power of influencers in reaching the targeted audience makes it a major tool for creating brand awareness and brand promotion. This research aims to determine the efficacy of social media influencer marketing among the residents of Kerala. Further, this study intends to determine consumer perceptions on social media influencer marketing in Kerala, and also to analyse the type of product that is most frequently purchased as a result of influencer marketing in the state. Therefore, this study will aid marketers in assessing the impact of influencer marketing in Kerala utilising Instagram influencers. The research incorporates both primary and secondary data. Online questionnaires will be used to collect primary data. Secondary data will be gathered from several sources, including articles, books, journals, and the internet. Keywords: Social Media, Instagram, Influencer Marketing, Consumer Behaviour, Brand Awareness